Reading Comprehension Strategies for University Students - Wankong, Anchanida (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 2 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2018)
The objective of this article was to study reading strategies is a key element in developing student comprehension. At present, using reading strategies have become important factors in learning language especially reading skill. The process of comprehension reading strategies has obtained particular attention. In addition, students understand the role of reading strategies will be received the beneficial in language learning. Therefore, the instructors need to design and prepare effective reading comprehension strategies. Teaching reading strategies is the important for students in order to improve reading skills in language classroom.